A holobiont birth narrative: the epigenetic transmission of the human microbiome - Gilbert, Scott F. (Frontiers in Genetics, 2014)
This essay plans to explore, expand, and re-tell the human birth narrative. Usually, human birth narratives focus on the origins of a new individual, focusing on the mother and fetus. This essay discusses birth as the origin of a new community. For not only is the eukaryotic body being reproduced, but so also are the bodies of its symbiotic microbes and so is the set of relationships between these organic components. Several parts of the new narrative are surprising: (1) bacterial symbionts might cause some of the characteristics of pregnancy and prepare a symbiotic community for transfer; (2) the first bacterial colonizers of the mammalian organism my enter the fetus prior to the lysing of the amniotic membrane and birth; (3) the same signals that often cause immunological attack against a microbe may serve under these conditions to signal homeostatic stability between symbiont and host; and (4) the mother may actively provide substances that promote the growth and settlement of helpful bacteria. The birth of the holobiont exemplifies principles of co-evolution, co-development, niche construction, and scaffolding. Birth is nothing less than the passage from one set of symbiotic relationships to another.